Effects of pits of different ages on ethyl acetate and its metabolism-related microorganisms during strong-flavor Baijiu fermentation - Zhang, Jing; Duan, Yunxuan; Lin, Yang; Chen, Jing; Cheng, Jie; Song, Chuan; Zuo, Jincen; Zhang, Suyi; Zuo, Yong (Frontiers in Microbiology, 2025)
The esters are the most important flavor components in Baijiu as their species and content decide the style of Baijiu. During the formation of esters, pits play important roles. In this study, the main esters and their related microorganisms in different years of pits (5, 35 and 100 years) of strong-flavor Baijiu were comprehensively researched by headspace solid-phase microextraction gas chromatography mass spectrometry (HS-SPME-GC-MS) and amplicon sequencing. A total of 690 bacterial genera and 155 fungal genera were detected. The microbial composition of ZPs (fermented grains) from 100 years pit was the most abundant at the genus level. A total of 177 volatile flavor components were observed, including 80 esters, 42 alcohols, 21 acids, 10 ketones and 11 aldehydes. Ethyl acetate was the lowest and ethyl caproate was relatively high in 100 years pit. 15 genera, including Lactobacillus, Pichia, Issatchenkia, Saccharomyces, and Aspergillus, were positively related to the formation of four major esters and their precursors. The research demonstrated that 100 years pit was benefit for maintaining microbial diversity and controlling ethyl acetate. This study is helpful for understanding the microbial composition and succession in the fermentation process of strong-flavor Baijiu, and revealing the complex relationships between dominant genera, physicochemical properties and volatile flavor components.